Effect of Coal Tar on the Properties of Butadiene–Nitrile Rubbers - Sevost’yanova, K.A.; Omasheva, A.V.; Baikenov, M.I.; Tazhbaev, E.M. (Allerton Press, 2016)
The analysis of coal tar as a by-product of a merchant-coke plant (Karaganda) was carried out for the use of this tar as a plasticizer of rubber compounds. The replacement of bitumen by this tar as a rubber constituent in a weight ratio of 1:10 showed that the kinetics of vulcanization was noticeably accelerated and rubber characteristics such as conditional tensile strength, hardness, freeze-proof factor, and relative residual deformation were improved. It was found that the derivatives of phenol as the constituents of this tar exerted a considerable effect on the acceleration of the vulcanization process. In connection with this, the dephenolization of the product was performed, and it was used in a rubber formulation in the same ratio; as a result, the best characteristics of frost resistance, resistance to a hostile environment (an isooctane–toluene mixture),and ultimate elongation were obtained.